Last chance for wildlife: making tourism count for conservation. Issue 5 (4th May 2023) - Hehir, Christy; Scarles, Caroline; Wyles, Kayleigh J.; Kantenbacher, Joe
Abstract: Nature-based tourism offers the opportunity for tourists to see first-hand both wildlife and the conservation efforts of organisations and individuals to protect habitats and species. Whilst recent studies hint that tourism can prompt visitors to provide philanthropic support for conservation, studies to-date have focused on behavioural intentions within specific case studies rather than actual behaviour, thereby limiting generalisability and explanatory scope. Consequently, little is known if and why individuals donate more after nature-based tourism. An online questionnaire, which included both quantitative and qualitive measures, explored key predictors of what triggers tourists to engage in philanthropic behaviour. Through a collaboration with two leading UK adventure travel companies, 924 participants' travel patterns and donation histories were examined to assess the role tourism plays in prompting new donations. Findings confirm, first, that travel to last chance destinations prompts higher instances of new philanthropy compared to other international and domestic trips; second, that other key factors, including the importance of stronger identity with nature and/or first-time visitation, influence new philanthropic support. Alongside the scholarly contributions, this study provides actionable guidance on how to encourage philanthropic behaviour working with both tour-operators and non-profit organisations.